(3GdJYhjV GdfbOj dQUjO GdELGRGJ GdEYJjGOjI HYO GfJgGA GdNOeIs - (3YHO GdZaGQ GHQGgje(B, (3ehSis ((3GdbGgQI(B:s (3OGQ GdcJH GdbGfhfjI(B,s, 2001)
(3GdgOa ef GdELGRGJ hCfhGYgG heYfi GdJYhjV GdfbOj(B- (3hXGFa GdeSJMbjf ddJYhjV(B- (3efGW GdESJMbGb ddJYhjV(B- (3TQhW GSJMbGb GdJYhjV(B- (3GdGTNGU GdeSJMbjf dbjeI GdJYhjV Yf QUjO GdELGRGJ GdEYJjGOjI(B- (3cjajI MSGH GdJYhjV(B- (3JbGOe GdMb aj GdJYhjV(B- (3GdeMceI GdeNJUI hGdELQGAGJ GdJWHjbGJ GdbVGFjI ddCMcGe hGdaJGhi(B.s
Keywords: (3GdJYhjV GdfbOjs; (3bGfhf GdYeds